Heightened Levels of Lignin and Flavonoids Coupled with the Absence in Sulfate-Reducing Bacteria Influencing the Non-Trunking Phenotype in Sago Palms (Metroxylon sagu Rottb.) - Fifi Hafizzah, Pendi; Hasnain, Hussain; Hairul Azman, Roslan; Mohd Effendi, Wasli; Zainab, Ngaini; Nur Ezzati, Hamdin; Norzainizul, Julaihi (Persatuan Genetik Malaysia, 2025)
Metroxylon sagu Rottb. is an important economic commodity crop in Sarawak, Malaysia. High demand for sago starch has initiated the state’s government to introduce sago palm cultivation to meet both local and overseas needs. Some plantations reported dwarf (non-trunking) sago palms after ten years of cultivation. Several studies have been conducted to address this matter, however, the biological mechanism underlying this problem is still scarce. In addition, information on soil properties at sago palm plantation is also limited. This study aims to identify the enriched genes and enzymatic pathways expressed in non-trunking and to differentiate microbial taxonomy present in both trunking and non-trunking soil environments. Transcriptome sequencing on Illumina NovaSeq 6000 platform with DESeq2 analysis revealed a total of 2158 differentially expressed genes between trunking and non-trunking datasets with 1353 DEGs were upregulated and 805 DEGs were downregulated. KEGG pathways enrichment revealed phenylpropanoid and flavonoid biosynthesis were significantly upregulated suggesting heightened lignin and flavonoid synthesis in non-trunking sago palms. Soil taxonomy datasets sequenced with 16S and ITS1 on Illumina MiSeq platform revealed Acidobacteria, Proteobacteria, and Actinobacteria were dominant bacterial phyla in trunking sago palm rhizosphere whilst phylum Ascomycota dominates both sampling sites. These comparative analyses will provide insight into the transcriptome of trunking and non-trunking palms and the associated taxonomic community composition in sago palms cultivated in peat soil.